(untitled) (Research, Society and Development, 2020)
Objective: to analyze the perception of quality of life in individuals with chronic Chagas disease. Method: quantitative exploratory study, carried out through a questionnaire with sociodemographic, environmental and clinical questions and with the World Health Organization Quality of Life, for the assessment of quality of life, applied to 184 individuals diagnosed with the disease, living in an endemic area of ​​Malhada -Bahia in 2018. Data analysis was performed using the statistical software SPSS 22®, applying the Chi-square and Fisher’s exact tests to assess the existing association. The variables were introduced in the multiple logistic regression model through the stepwise procedure with backward, those that remained significant were kept in the model and the values ​​obtained were expressed in odds ratios. Results: in the studied population, there was a predominance of women, in conditions of socio-environmental and socio-economic vulnerabilities, exemplified by low education, income and difficult access to public basic sanitation services. The percentage of Chagas patients who do not assess quality of life as good was 56.5%. In the final evaluation model, the use of medications, hospitalization and smoking was associated with a reduction in quality of life. Final considerations: Chagas disease is linked to rural populations, in socioeconomic vulnerability, whose difficulty in accessing public services interferes with the quality of life.